Hollow oaks and beetle functional diversity: Significance of surroundings extends beyond taxonomy. Issue 2 (8th January 2020) - Wetherbee, Ross; Birkemoe, Tone; Skarpaas, Olav; Sverdrup‐Thygeson, Anne
Abstract: Veteran hollow oaks ( Quercus spp.) are keystone structures hosting high insect diversity but are declining in numbers due to intensification of land use and the abandonment of traditional management. The loss of this vital habitat is resulting in a reduction of biodiversity, and this likely has consequences for ecosystem functioning, especially if functional diversity is reduced. A considerable amount of research has been done on predictors of beetle taxonomic diversity in veteran oaks, but predictors of functional diversity have remained largely unexplored. The aim of this study was to establish whether the features and surroundings of veteran oaks are related to functional diversity within three functional groups of beetles (decomposers, predators, and flower visitors) and determine whether species richness and functional diversity within the groups are dependent on the same predictors. Sampling was carried out intermittently between 2004 and 2011 on 61 veteran oaks in Southern Norway. Of the 876 beetle species that were collected, 359 were determined to be decomposers, 284 were predators, and 85 were flower visitors. Species richness and functional diversity in all groups were consistently higher in traps mounted on veteran oaks in forests than in open landscapes. However, additional predictors differed between groups, and for species richness and functional diversity. Decomposer species richness responded to tree vitality, while functional diversity responded to habitat connectivity, predator species richness responded to regrowth of shrubs while functional diversity responded to tree circumference, and flower visitor richness and functional diversity did not respond to any additional predictors. Previous studies have found that the features and surroundings of veteran oaks are important for conservation of taxonomic diversity, and the results from this study indicate that they are also important for functional diversity within multiple functional groups. Abstract : Veteran hollow oaks (Quercus spp.) are keystone structures hosting high insect diversity. The aim of this study was to establish whether the features and surroundings of these trees are related to functional diversity of beetles within three functional groups (decomposers, predators, and flower visitors) and determine whether species richness and functional diversity within the groups are dependent on the same predictors. Previous studies have found that veteran oak's features and surroundings are important for conservation of taxonomic diversity, but the results from this study clearly indicate that they are also important for supporting multiple ecosystem functions.